A DNA Nanoflower‐Assisted Separation‐Free Nucleic Acid Detection Platform with a Commercial Pregnancy Test Strip. Issue 47 (18th October 2021) - Qi, Lijuan; Yang, Meiting; Chang, Dingran; Zhao, Wenjing; Zhang, Sicai; Du, Yan; Li, Yingfu
Abstract: There is a constant drive for affordable point‐of‐care testing (POCT) technologies for the detection of infectious human diseases. Herein, we report a simple platform for DNA detection that takes advantage of four techniques: commercially available pregnancy test strips (PTS), amplicon generation via loop‐mediated isothermal amplification (LAMP), toehold‐mediated strand displacement, and noncovalent immobilization of DNA on paper surface with DNA nanoflowers. This simple, separation‐free platform is highly specific, as demonstrated with the detection of rtL180M, a single‐nucleotide polymorphism observed in hepatitis B virus (HBV) associated with antiviral drug resistance. It is very sensitive, capable of detecting the targeted mutation at 2 copies μL −1 . It is able to correctly identify the unmutated and rtL180M genome types of HBV in clinical samples. Given its wide adaptability, we expect this platform can be easily modified for the detection of genetic variations associated with various pathogens and human diseases. Abstract : Bound then free: DNA nanoflowers are used to immobilize a human chorionic gonadotropin (hCG)‐modified DNA strand (hCG‐DNA), which can be released by DNA amplicons from loop‐mediated isothermal amplification (LAMP) via toehold‐mediated strand displacement (TMSD) and detected with an off‐the‐shelf pregnancy test strip (PTS) in a separation‐free one‐step process. The method is capable of achieving single‐base resolution.